2006
DOI: 10.1007/s11010-005-9020-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative antioxidant activity of tocotrienols and the novel chromanyl-polyisoprenyl molecule FeAox-6 in isolated membranes and intact cells

Abstract: Oxidative stress plays a pivotal role in the pathogenesis of several chronic diseases and antioxidants may represent potential tools for the prevention of these diseases. Here, we investigated the antioxidant efficiency of different tocotrienol isoforms (alpha-, delta-, gamma-tocotrienols), and that of FeAox-6, a novel synthetic compound which combines, by a stable covalent bond, the chroman head of vitamin E and a polyisoprenyl sequence of four conjugated double bonds into a single molecule. The antioxidant e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 43 publications
2
49
0
Order By: Relevance
“…The present study, using a chronic experimental setup where animals were fed TRF and tocotrienols for a period of 4 wk, confirmed this previous observation and further demonstrated that tocotrienol isomers present in TRF differentially stabilize proteasomes with the ␦-isomer being the most protective and ␣-and ␥-isomers providing protection midway between baseline and postischemic hearts, which surprisingly is reverse to their respective cardioprotective efficacies. It is not clear whether this is related to the differential regulation of proteasome subunits, but it could be related to differential compartmentalization (30) or antioxidant potential, with the ␦-isomer reported to be the most effective (19).…”
Section: Discussionmentioning
confidence: 99%
“…The present study, using a chronic experimental setup where animals were fed TRF and tocotrienols for a period of 4 wk, confirmed this previous observation and further demonstrated that tocotrienol isomers present in TRF differentially stabilize proteasomes with the ␦-isomer being the most protective and ␣-and ␥-isomers providing protection midway between baseline and postischemic hearts, which surprisingly is reverse to their respective cardioprotective efficacies. It is not clear whether this is related to the differential regulation of proteasome subunits, but it could be related to differential compartmentalization (30) or antioxidant potential, with the ␦-isomer reported to be the most effective (19).…”
Section: Discussionmentioning
confidence: 99%
“…The differential cell uptake of vitamin E forms could involve specific transporters such as the organic anion transport system (Negis et al 2007), but also direct membrane transfer and intramembrane diffusion and interaction mechanisms that appear to favor the uptake and bioactivity of HM T3 forms (Palozza et al 2006). The rapid and massive uptake of d-T3 and in general of HM forms in cancer cells may influence the lipid structure and key functional domains of the plasmalemma (Atkinson et al 2010).…”
Section: Metabolite Formation and Activitymentioning
confidence: 99%
“…It represents a family of compounds that is divided into two subgroups called tocopherols and tocotrienols, which act as important antioxidants that regulate peroxidation reactions and control free-radical production within the body (Palozza et al, 2006(Palozza et al, , 2008. This family of compounds has eight different isoforms that belong to two categories: four saturated analogues (α, β, γ, and δ) called tocopherols and four unsaturated analogues referred to as tocotrienols.…”
mentioning
confidence: 99%